1995
DOI: 10.1111/j.1600-0536.1995.tb00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact sensitivity to menthol and peppermint in patients with intra‐oral symptoms

Abstract: We report 12 cases of contact sensitivity to the flavouring agents menthol and peppermint oil in patients presenting with intra-oral symptoms in association with burning mouth syndrome, recurrent oral ulceration or a lichenoid reaction. The patients were referred from the Glasgow Dental Hospital over a 4-year period for assessment of the possible contribution of contact sensitivity to their complaints. 5 patients with burning mouth syndrome demonstrated contact sensitivity to menthol and/or peppermint, with 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] However, few studies have used larger oral allergen screening series that, in addition to metals, included flavorings, preservatives, and dental acrylates. [12][13][14][15][16] We report the results of patch tests to the 85 allergens in our oral screening series.…”
mentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11] However, few studies have used larger oral allergen screening series that, in addition to metals, included flavorings, preservatives, and dental acrylates. [12][13][14][15][16] We report the results of patch tests to the 85 allergens in our oral screening series.…”
mentioning
confidence: 98%
“…For example, peppermint or cinnamon oil are used to flavour toothpaste or are applied in dental care and have been shown to induce contact allergy [33, 34]. Other sources may be massage oils, which contain oil of cinnamon and cloves [35], and many cosmetics or essential oils are derived from ‘spicy’ sources, for instance star anise [36], sesame seed [37], vanilla [38] or rosemary [39].…”
Section: Who Is Affected By Spice Allergy?mentioning
confidence: 99%
“…He improved quickly after avoiding mint-flavored toothpastes. Morton et al [54] reported the largest series of patients with positive reactions to menthol and/or peppermint. They tested 512 patients complaining of intraoral symptoms with a large series of substances including menthol and peppermint oil.…”
mentioning
confidence: 99%
“…Menthol and menthol-containing substances have resulted in dermatitis [43][44][45][46], perioral eczema [44,[47][48][49][50], cheilitis [49][50][51][52][53], stomatitis [54,55] and other intraoral reactions [48,51,54,55]. Allergic contact dermatitis from mint was first suggested by Sams in 1940 [43] as occupational allergic hand dermatitis in 2 Florida bartenders, who made drinks containing locally grown European mint (Mentha citrata).…”
mentioning
confidence: 99%
See 1 more Smart Citation